Analisis Pengaruh Label Halal, Persepsi Harga, dan Kualitas Produk terhadap Keputusan Pembelian Kosmetik Wardah - Widiyastuti , Radita; Hamid , Homaidi (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2022)
This study aims to determine and analyze the effect of halal labels, price perceptions, and product quality on Wardah cosmetic purchasing decisions. The approach used in this research is a quantitative approach. The population in this study were customers of Wardah cosmetics in Sumbawa Regency. The sample taken was 100 respondents using a nonprobability sampling technique, then in selecting population members using a purposive sampling method with the following criteria: (1) Wardah cosmetic users in Sumbawa Regency; (2) Age 15 – 34 years; (3) Have bought or used Wardah cosmetic products. This study used a questionnaire to collect respondent data. The data analysis technique in this study uses the Multiple Linear Regression Technique, Classical Assumption Test, T Test and F Test and the Coefficient of Determination. The results of this study are that the halal label has a positive and significant effect on purchasing decisions for Wardah cosmetics, price perceptions have no negative and significant effect on purchasing decisions for Wardah cosmetics, product quality has a positive and significant effect on purchasing decisions for Wardah cosmetics, and simultaneously it is known that halal labels, Perceptions of price and product quality have a significant effect on the decision to purchase Wardah cosmetics.